Perspectives of illicit marijuana growers and traders on commercial legalisation of marijuana in South Africa: considerations for policy formulation - Emmanuel Manu; Mbuyiselo Douglas; Mohlomi Jafta Ntsaba; Elvis Enowbeyang Tarkang (BMC, 2021)
Abstract Background Over the years, there has been a clarion call for legalising marijuana cultivation and trading for commercial purposes in South Africa. Proponents of the call argue that the criminalisation of commercial marijuana cultivation and trading has failed to halt illicit marijuana cultivation and trading. However, the views of those who economically benefit from the illicit marijuana trade on its legalisation remain empirically unsolicited. Objective This study aimed to solicit the views of illegal marijuana growers and traders from two selected communities in the Eastern Cape Province of South Africa regarding the commercial legalisation of marijuana cultivation and trading to inform policy on the debate. Methods In-depth key informant interview approach was used to interview 18 purposively sampled participants that were selected through the snowball sampling technique. The data were analysed using the thematic content analysis approach. Results Participants had both positive and negative perceptions of the possible legalisation of marijuana cultivation and trading. On the positive side, participants indicated freedom from police, the opportunity to grow marijuana on a larger scale, capital acquisition for commercial marijuana cultivation and trading, and regulation of marijuana prices through unionisation as some of the benefits they would derive from the commercial legalisation of marijuana cultivation and trading. On the negative side, loss of their source of livelihood, fall in the price of marijuana and perceived increase in school drop-out rates were the concerns raised. Conclusion While participants relished improvement in their economic fortunes upon commercial legalisation of marijuana cultivation and trading, they were also apprehensive about this policy due to the perceived consequences it may have on their livelihoods and communities. We, therefore, recommend that future discussions of the commercial legalisation of marijuana cultivation and trading in South Africa should be done in consultation with illicit marijuana growers and traders to ensure that their interests are safeguarded by such a policy.